2020
DOI: 10.1073/pnas.1922216117
|View full text |Cite
|
Sign up to set email alerts
|

Global epigenomic analysis of KSHV-infected primary effusion lymphoma identifies functional MYC superenhancers and enhancer RNAs

Abstract: Enhancers play indispensable roles in cell proliferation and survival through spatiotemporally regulating gene transcription. Active enhancers and superenhancers often produce noncoding enhancer RNAs (eRNAs) that precisely control RNA polymerase II activity. Kaposi’s sarcoma-associated herpesvirus (KSHV) is a human oncogenic gamma-2 herpesvirus that causes Kaposi’s sarcoma and primary effusion lymphoma (PEL). It is well characterized that KSHV utilizes host epigenetic machineries to control the switch between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 62 publications
2
26
0
Order By: Relevance
“…We identified >8000 enhancer–promoter, enhancer–enhancer, and promoter–promoter interactions in these cell lines. The connectome linked SEs to dependency factors MYC, IRF4, MCL, MDM2, and CCND2 66 .…”
Section: Discussionmentioning
confidence: 99%
“…We identified >8000 enhancer–promoter, enhancer–enhancer, and promoter–promoter interactions in these cell lines. The connectome linked SEs to dependency factors MYC, IRF4, MCL, MDM2, and CCND2 66 .…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, the sequence variability of these regions and the strict time-dependence of their transcription could be instrumental to adaptive features; however, these same features make these regions susceptible to become dysfunctional or to be the targets of pathogenic interaction. In some instances, these detrimental interactions come from outside the cell, such as in the case of EBV interference with host transcription (Mechelli R., 2021, Accepted; Park et al, 2020), and the pathogenic consequences of vitamin D deficiency; in other cases, the dysfunction develops within the cell, such as the tumorigenic activity of AID in B cells (Meng et al, 2014; Qian et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we found that ODC1 is slightly upregulated in iSLK.BAC16 vs SLK cells (Fig 1F). In contrast, KSHV lytic induction resulted in the decrease of ODC1 protein in Dox-treated iSLK.BAC16 (Fig 1G), likely because c-Myc is silenced due to KSHV lytic reactivation [47,48]. Consistently, we also observed that ODC1 mRNA level also decreased at 3 dpi in primary tonsillar B cells isolated from healthy donors, known to be susceptible to KSHV infection and maintain active lytic replication [49], which were spinoculated with KSHV.BAC16 viruses, followed by RT-qPCR analysis (Fig 1H).…”
Section: Kshv Dynamically Modulates Intracellular Polyaminesmentioning
confidence: 95%